2019
DOI: 10.11130/jei.2019.34.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Exports and Non-Tariff Measures: Testing for Heterogeneous Effects at the Product Level

Abstract: With international trade tariffs at historically low levels today, non-tariff measures (NTMs) play an important-and growing-role in global trade policy. Concerns about shifts in global trade policy agendas are on the rise. In this paper, we rely on a gravity model and focus on Chinese exports with two aims: the first is to test for heterogeneous effects of technical NTMs versus non-technical NTMs; the second is to verify whether the NTM's effect is influenced by the type of good (final good vs. intermediate or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 44 publications
3
19
1
Order By: Relevance
“…However, these results contradict those of Santeramo et al [37], who found that INSP and TBT encouraged wine imports for China. In addition to Santeramo et al [37], several other researchers have proved that NTMs do not necessarily harm trade; they can also have positive impacts on trade [20,23,38]. Ghodsi and Stehrer [23] found that SPS measures imposed by the EU significantly increased dairy trade values and quantities.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…However, these results contradict those of Santeramo et al [37], who found that INSP and TBT encouraged wine imports for China. In addition to Santeramo et al [37], several other researchers have proved that NTMs do not necessarily harm trade; they can also have positive impacts on trade [20,23,38]. Ghodsi and Stehrer [23] found that SPS measures imposed by the EU significantly increased dairy trade values and quantities.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Ghodsi and Stehrer [23] found that SPS measures imposed by the EU significantly increased dairy trade values and quantities. Timini and Conesa [38] explored the impact of technical and non-technical NTMs in China and found that technical NTMs have a positive impact on trade by increasing consumer confidence in and the technical capabilities of Chinese exporters. Non-technical NTMs were found to be very stringent for final goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the spirit of Dhingra et al (2018), but further exploiting the detailed information available on the specific provisions included in the agreement, 16 we focus on those measures that are included in the agreement and, following the recent literature, are more likely to have an effect on bilateral trade flows. These are summarized in Mattoo et al (2020,) 17 and include: tariffs and non-tariff measures (Fontagné et al, 2015;Murina and Nicita, 2017;Timini and Conesa, 2019), trade in services (Blyde and Sinyavskaya, 2007); state-owned enterprises (Kowalski et al, 2013); public procurement (Kim, 2010); intellectual property rights (Maskus and Ridley, 2016); competition policy (Motta and Onida, 1997;Liu and Ye, 2019); investment, including movement of capital (Busse, 2010); environment (Brandi et al, 2020); and labour markets (Timini et al, 2020). Table A.1 in the Appendix reports the complete list of provisions on which we impose a restriction, and those where we remain agnostic.…”
Section: Partial Equilibriummentioning
confidence: 99%
“…In the spirit of Dhingra et al (2018), but further exploiting the detailed information available on the specific provisions included in the agreement, 16 we focus on those measures that are included in the agreement and, following the recent literature, are more likely to have an effect on bilateral trade flows. These are summarized in Mattoo et al (2020,) 17 and include: tariffs and non-tariff measures (Fontagné et al, 2015;Murina and Nicita, 2017;Timini and Conesa, 2019), trade in services (Blyde and Sinyavskaya, 2007); state-owned enterprises (Kowalski et al, 2013); public procurement (Kim, 2010); intellectual property rights (Maskus and Ridley, 2016); competition policy (Motta and Onida, 1997;Liu and Ye, 2019); investment, including movement of capital (Busse, 2010); environment (Brandi et al, 2020); and labour markets (Timini et al, 2020). Table A.1 in the Appendix reports the complete list of provisions on which we impose a restriction, and those where we remain agnostic.…”
Section: Partial Equilibriummentioning
confidence: 99%